The Effect of Work-Life Balance And Job Satisfaction On The Performance of Employees At The Klampis Ngasem Community Health Center In Surabaya City - Moch. Rafli Islamy Yusuf; Dwi Widi Hariyanto; Naam fajar basroni; Iwan wahyu susanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2026)
This study examines the influence of work-life balance and job satisfaction on the performance of public health center (Puskesmas) employees. Employee performance is critical in ensuring quality healthcare services, making it important to identify factors that affect it. The research uses a quantitative survey approach, collecting primary data via questionnaires from Puskesmas employees and analyzing it with multiple linear regression. The results show that work-life balance has a positive and significant effect on employee performance, indicating that employees with better balance between work and personal life tend to perform better. Meanwhile, job satisfaction also has a positive effect but is not statistically significant, suggesting that feeling satisfied at work does not necessarily lead to a notable improvement in performance.